Bulharská etnologie po roce 1989 - Machová, Barbora (Lidé města, 2008)
After the Velvet Revolution, our rich contacts with Bulgarian ethnologists were interrupted; since then, Bulgarian ethnology has been almost unknown in the Czech Republic. This article gives some basic information about how Bulgarian ethnology has developed throughout the 1990’s and after the year 2000 up to the present day. It presents the general tendencies in the development of ethnology (and anthropology) in this period as the heritage of the two most important trends in Bulgarian ethnological studies – ethnography and folklore studies, as well as the newly booming cultural anthropology. It also draws attention to the central ethnological institutions – two institutes of the Bulgarian Academy of Sciences – the Ethnographic Institute and Museum, and the Institute of Folklore Studies - and to their main projects: to ethnology and anthropology as studied at universities and also publications, especially of periodical issues. A part of the article is dedicated to the most significant persona specializing in ethnology in Bulgaria since the end of the 1970’s up to the present day, Professor Todor Ivanov Zhivkov. The article contains a list of ethnographic workplaces with addresses and web sites.